Detection of Histone H2AX Phosphorylation on Ser‐139 as an Indicator of DNA Damage. Issue 1 (22nd April 2019) - Zhao, Hong; Huang, Xuan; Halicka, H. Dorota; Darzynkiewicz, Zbigniew
Abstract: This unit describes immunocytochemical detection of histone H2AX phosphorylated on Ser‐139 (γH2AX) to reveal DNA damage, particularly when the damage involves the presence of DNA double‐strand breaks (DSBs). These breaks often result from DNA damage induced by ionizing radiation or by treatment with anticancer drugs such as DNA topoisomerase inhibitors. Furthermore, DSBs are generated in the course of DNA fragmentation during apoptosis. The unit presents strategies to distinguish radiation‐ or drug‐induced DNA breaks from those intrinsically formed in untreated cells or associated with apoptosis. The protocol describes immunocytochemical detection of γH2AX combined with measurement of DNA content to identify cells that have DNA damage and concurrently to assess their cell‐cycle phase. The detection is based on indirect immunofluorescence using FITC– or Alexa Fluor 488–labeled antibody, with DNA counterstained with propidium iodide and cellular RNA removed with RNase A. © 2019 by John Wiley & Sons, Inc.